Profil Self Regulation Mahasiswa Pendidikan Matematika FKIP Universitas Riau di Masa Pandemi Covid-19 - Hesty Marwani Siregar; Syarifah Nur Siregar (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This research aims to determine the description of students’ self-regulation of Mathematics Education FKIP at the Universitas Riau during the Covid-19 pandemic. The subjects in this study were 121 students of Mathematics Education, FKIP, Universitas Riau. This research uses a descriptive quantitative approach. The data obtained from students was the score of self-regulation of Mathematics Education students, FKIP, Universitas Riau during the Covid-19 pandemic. The research that was conducted showed that the students' self-regulation were at a moderate level as many as 21 people (17.36%), at a high level as many as 80 people (66.12%), and at a very high level as many as 20 people (16.53%). Meanwhile, the achievement of students' self-regulation for each indicator consisted of a goal-setting indicator of 85.74% with a good category, an indicator of environment structuring of 80.48% in a good category, an indicator of task strategies of 73.17% in a fair category, an indicator of time management is 63.22%% in a fair category, an indicator of seeking help is 73.76% in a fair category, and self-evaluation indicator is 87.6% in a very good category. Based on the self-regulation category of each student and the percentage of self-regulation achievement for each indicator, it can be said that the students of Mathematics Education FKIP Universitas Riau were able to adapt while taking online classes during the Covid-19 pandemic by having good self-regulation.